2022
DOI: 10.1093/molehr/gaac003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals myometrial topologically associated domains linked to the onset of human term labour

Abstract: Changes in cell phenotype are thought to occur through the expression of groups of co-regulated genes within topologically associated domains (TADs). In this paper we allocate genes expressed within the myometrium of the human uterus during the onset of term labor into TADs. Transformation of the myometrial cells of the uterus into a contractile phenotype during term human labor is the result of a complex interaction of different epigenomic and genomic layers. Recent work suggests that the transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…PSMA3-AS1 is also reported to regulate oxidative stress and GSH-Px activities to promote gastric cancer progression (21). Based on the transcriptomic analysis, a previous study has revealed that PSMA3-AS1 is identified as one of the hub genes implicated in co-regulatory networks that drive a myometrial transformation and thus produce an estrogen-sensitive phenotype in pregnant women (22). However, the mechanisms underlying the potential of PSMA3-AS1 in premature delivery…”
Section: Introductionmentioning
confidence: 99%
“…PSMA3-AS1 is also reported to regulate oxidative stress and GSH-Px activities to promote gastric cancer progression (21). Based on the transcriptomic analysis, a previous study has revealed that PSMA3-AS1 is identified as one of the hub genes implicated in co-regulatory networks that drive a myometrial transformation and thus produce an estrogen-sensitive phenotype in pregnant women (22). However, the mechanisms underlying the potential of PSMA3-AS1 in premature delivery…”
Section: Introductionmentioning
confidence: 99%